2019
DOI: 10.1088/1748-0221/14/08/p08006
|View full text |Cite
|
Sign up to set email alerts
|

The physics of radiochromic process: one calibration equation for all film types

Abstract: A: A unique calibration equation for all radiochromic film types is proposed. The determination of this equation comes from an analogy that the authors made between the radiochromic and photographic processes. Photography dynamics is ruled by a differential equation, the logistic equation, describing phenomena of growth versus competition. A solution of the logistic equation is the Green-Saunders equation which was used for the first time by the same authors in a previous referred work for the calibration of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These universal calibrations are valid since their parameters are related to the physical mechanism associated with film exposure, namely, the activation of the crystalline polydiacetylene molecules in the active layer. Similarly, Casolara et al [49,50] have shown parallels between the responses of radiochromic and photographic film and therefore the ability to describe the dynamic developing process of both through a general equation to create a universal calibration curve. As these universal calibration curves are described by parameters which depend on the response of the sensitive material in the film, and most films share the same active material, they are broadly applicable across various types of film.…”
Section: Discussionmentioning
confidence: 94%
“…These universal calibrations are valid since their parameters are related to the physical mechanism associated with film exposure, namely, the activation of the crystalline polydiacetylene molecules in the active layer. Similarly, Casolara et al [49,50] have shown parallels between the responses of radiochromic and photographic film and therefore the ability to describe the dynamic developing process of both through a general equation to create a universal calibration curve. As these universal calibration curves are described by parameters which depend on the response of the sensitive material in the film, and most films share the same active material, they are broadly applicable across various types of film.…”
Section: Discussionmentioning
confidence: 94%
“…This energy value results from the initial beam energy of (18.1±0.3) MeV (that was measured in previous studies 21,22 ) to which the energy loss (755 keV) in the extraction window is subtracted. The beam uniformity in the scintillators' position was evaluated to be <2% in horizontal and vertical directions by means of measurements with calibrated EBT-XD Gafchromic films 23,24 . The measurement runs were performed by delivering short beam shots of the duration of about 2 s to the GAGG, BaF 2 and PS scintillators in the range (12-626) Gy/s and to BaF 2 scintillator up to 10 kGy/s.…”
Section: Independent Dosimetry Systemmentioning
confidence: 99%
“…Santos et al have recently reviewed the most of the functional forms proposed so far for RCF calibration [18]. These include rational, power, polynomial, and logarithmic functions, as well as universal functions applicable for several RCF types and dose ranges [90,91]. It should be noted that the choice of the calibration equation depends on the dynamic range and sensitivity required by the measurement as well as on the physical quantity used to evaluate the RCF darkening (netOD, raw PV, etc.…”
Section: Flatbed Scannersmentioning
confidence: 99%